Perbandingan Pengetahuan, Sikap , dan Perilaku Mengenai Demam Berdarah antara Kelurahan Sosromenduran dan Pringgokusuman, Kecamatan Gedongtengen, Kodia Yogyakarta - Emy Febryana, Hasti Apriyanti, Migi Pradysta K., Gina Anindyajati, Aike Karunia P.P (Fakultas Kedokteran Universitas Gadjah Mada, 2010)
Background: Dengue Hemorrhagic Fever (DHF) is currently still one of the main health problems in the Indonesian community with increasing number of patients each year. The primary preventive measure for this disease is the 3M method (Drain, Bury and Cover/Close). This program can be assessed by evaluating the knowledge, attitude, and behavior of the community towards the disease. Every year, Gedongtengen District records one of the highest numbers of cases of DHF in Yogyakarta.Objective: To investigate the trend in knowledge, attitude and behavior towards DHF between Sosromenduran and Pringgokusuman Sub districts in Yogyakarta.Method: This research was a quantitative descriptive study conducted at Home Residents (Rumah Warga) 04 and 06 of Sosromenduran Sub district and Home Residents (Rumah Warga) 03 of Pringgokusuman Sub district. Thirteen respondents from Sosromenduran Sub district dan 35 from Pringgokusuman Sub district were enrolled. To obtain the primary data, questionnaires were randomly distributed to the respondents which fulfill the sampling criteria. The respondents must be a family member or the head of the family residing of each sub district, age >15 years old. The social economic status, occupation, sex and level of education are not discerned in this study. The correlation between variables was analyzed using Pearson or Spearman correlation test.Result: There is similarity in demographic characteristic between respondents of Sosromenduran and Pringgokusuman Sub districts. Knowledge with attitude of respondents have a negative correlation at Sosromenduran Sub district and positive at Pringgokusuman Sub district (r=-0,019; r=0,521). Knowledge with behavior have a negative correlation at Sosromenduran and Pringgokusuman Sub districts respectively (r= -0,139; r=-0,064). Attitude with behavior have a positive correlation at Sosromenduran and Pringgokusuman Sub districts respectively (r=0,315; r=0,05).Conclusion: The correlation between knowledge with behavior and attitude with behavior of respondents is not different from both sub districts. The correlation between knowledge with attitude of respondents is different from both sub districts.Keywords: dengue hemorrhagic fever, 3M, knowledge, attitude, behavior